2016
DOI: 10.3329/ijarit.v6i1.29208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potato (Solanum tuberosum L.) genotypes for resistance to late blight at Sinana Southeastern Ethiopia

Abstract: Late blight caused by Phytophthora infestans (Mont.) de Bary, is one of the most significant constraints to potato production in Bale high lands and other regions of Ethiopia. Hence, this requires to develop high yielding and late blight resistant varieties. Therefore, this study was conducted to determine host resistance of potato against Phytophthora infestans in order to develop late blight resistant/tolerant genotypes. The experiment was laid out in randomized complete block design with three replications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…For example, Gudene was released as resistant cultivar to late blight in 2006 by Holetta Agricultural Research Center and grown in the studied areas. However, the current findings indicated that Gudene became susceptible variety to late blight which is in agreement with the results found by Asefa et al (2016). This may be due to the changing behavior of the pathogen strains since many resistant varieties have been overcome by Phytophtera infestans in the past.…”
Section: Late Blight Managementsupporting
confidence: 92%
See 2 more Smart Citations
“…For example, Gudene was released as resistant cultivar to late blight in 2006 by Holetta Agricultural Research Center and grown in the studied areas. However, the current findings indicated that Gudene became susceptible variety to late blight which is in agreement with the results found by Asefa et al (2016). This may be due to the changing behavior of the pathogen strains since many resistant varieties have been overcome by Phytophtera infestans in the past.…”
Section: Late Blight Managementsupporting
confidence: 92%
“…Moreover, mismatch between the selection criteria that breeders and farmers use resulted in low number of improved varieties grown by farmers (Semagn et al, 2019). Releasing new improved varieties had been used as an option to minimize the losses due to late blight and to improve the quality of potato tubers in storage (Asefa et al, 2016). However, breeders in Ethiopia are not seen developing new varieties within short period since breeding for creating a new potato variety is slow and difficult (Stokstad, 2019).…”
Section: Potato Varieties Grown In the Studied Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Crop improvements made since the 1950s coupled with inexpensive agronomic inputs, such as fertilizers, pesticides, and water have allowed agricultural production to keep pace with human population growth (Brummer et al 2011). In Ethiopia, a number of improved potato varieties have been released by different research institutions; with major emphasis to wide adaptability, high tuber yield and late blight resistance (Asefa et al 2016). Since the registration of the first potato variety (AL-624) in 1987, more than 36 potato varieties were released by the research centers, higher learning institutions and private companies (Gebremedhin 2013;MANR 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, small scale potato chips processors are flourishing in cities and big towns. In developing the varieties, much emphasis was given to productivity per unit area and late blight reaction (Asefa et al, 2016) while less emphasis was given to processing quality and studies regarding effect of storage on process and nutritional quality are less probable to get in the country. To meet the demand for varieties suitable for processing industry and storable for longer periods and to keep market with minimum weight and nutritional loss is a very important to evaluate the fitness of the released varieties for processing and to incorporate processing quality as a yardstick in varietal development procedure.…”
Section: Introductionmentioning
confidence: 99%